2013
DOI: 10.1093/carcin/bgt348
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ERβ signaling via ERβ knockout or antagonist protects against bladder cancer development

Abstract: Epidemiological studies showed that women have a lower bladder cancer (BCa) incidence, yet higher muscle-invasive rates than men, suggesting that estrogen and the estrogen receptors, estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ), may play critical roles in BCa progression. Using in vitro cell lines and an in vivo carcinogen N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN)-induced mouse BCa model, we found that ERβ plays a positive role in promoting BCa progression. Knockdown of ERβ with ERβ-shRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…48 However, some data suggest expression of this receptor could promote bladder cancer progres sion. In in vitro and in vivo experiments, Hsu et al 49 showed that ERβ knockdown in nonmalignant urothe lial cells conferred resistance to 3methylcholanthrene induced malignant transformation. These authors also showed that ERβdeficient mice were less susceptible to BNNinduced bladder cancer than their wildtype counter parts.…”
Section: Gender Differences In Bladder Cancermentioning
confidence: 99%
“…48 However, some data suggest expression of this receptor could promote bladder cancer progres sion. In in vitro and in vivo experiments, Hsu et al 49 showed that ERβ knockdown in nonmalignant urothe lial cells conferred resistance to 3methylcholanthrene induced malignant transformation. These authors also showed that ERβdeficient mice were less susceptible to BNNinduced bladder cancer than their wildtype counter parts.…”
Section: Gender Differences In Bladder Cancermentioning
confidence: 99%
“…Knockdown of ER-b expression in both in vitro ER-bepositive human bladder cancer cell lines and in vivo carcinogen (N-butyl-N-(4-hydroxybutyl) nitrosamine)-induced mouse BC model resulted in suppression of cell growth and invasion, as well as decreased expression of Ki 67 (proliferation marker). 35 Furthermore, treatment of the cell lines with the ERbespecific antagonist PHTPP decreased cell growth and invasion, suggesting that ER-b may serve as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with other investigations that did not find bladder hypertrophy or histologic changes in untreated ERαKO or ERβKO mice. 22,23 We did not observe bladder enlargement in ERαKO male mice treated with T+E 2 , indicating that ERα is necessary for hormone-induced bladder enlargement. While the specific cell types and target tissues mediating this effect remain unknown, bladder outlet obstruction is related to prostatic enlargement in male mice treated with T+E 2 , and the bladder responds with hypertrophy and eventually decompensates.…”
Section: Discussionmentioning
confidence: 64%